The effectiveness of micro-learning in retail banking - Madden, M.; Govender, K.K. (South African Journal of Higher Education, 2020)
In order to remain competitive in a global technological revolution, the learning and development departments of businesses are focusing on the emerging concept of micro-learning, to support the fast-paced, multitask orientated and digitally savvy learners. A survey was conducted among 7 673 employees of one of the major retail banks in South Africa, to determine the effectiveness of micro-learning and establish whether micro-learning is effective, as well as identify gaps and recommend strategies to close them. Through inferential statistical analysis of the data, it was concluded that learners reacted positively to micro-learning, the acquired relevant knowledge using micro-learning which improved work performance and business metrics. Although the micro-learning programme was deemed effective for the vast majority (80%) of the participants, two gaps were identified, namely, micro-learning did not fully embrace the social tenet of learning, and it is also not exempt from the distractions that learners experience. It is recommended that any organisation pursuing a micro-learning programme should incorporate a social knowledge-sharing element into the programme and provide users with tools to develop self-control and self-regulation habits needed to conquer constant distractions.